Elektroninės valdžios paslaugų pakopų ir „E. deimanto“ modelių lyginamieji aspektai, jų tobulinimo koncepcinės kryptys - Limba, Tadas (Information & Media, 2011)
Straipsnyje išanalizuoti elektroninės valdžios paslaugų pakopų ir „E. deimanto“ modelių kūrimo bei taikymo viešojo administravimo institucijoje ypatumai, pranašumai ir trūkumai. Sukūrus šių modelių bendruosius požymius, jais remiantis atlikta elektroninės valdžios paslaugų pakopų ir „E. deimanto“ modelių lyginamoji analizė, pateiktos šių modelių tobulinimo koncepcinės rekomendacijos. Tyrimo originalumą pabrėžia elektroninės valdžios paslaugų modelių išsami koncepcinė analizė išskiriant šių modelių bendruosius požymius lyginamuoju aspektu. Nagrinėjant elektroninės valdžios paslaugų modelius, taikyti sisteminės analizės, koncepcinės lyginamosios analizės ir dinaminio modeliavimo metodai, kurie leido geriau atskleisti elektroninės valdžios paslaugų integravimo viešojo sektoriaus institucijose problemas ir jų tobulinimo galimybes. Atlikta elektroninės valdžios paslaugų pakopų ir „E. deimanto“ modelių lyginamoji analizė bei detaliai išanalizuotos pakopų modelių transformacijos į „E. deimanto“ modelį dinaminės kryptys leistų efektyviau integruoti naujai sukurtus holistinius procesus apimančius modelius įvairių šalių viešojo sektoriaus sistemose, reglamentuojant šių modelių taikymo ypatumus nacionaliniuose teisės aktuose.Comparative Aspects of Electronic Government Services’ Maturity and “E-Diamond” Models, the Conceptual Features of Their ImprovementTadas LimbaSummaryNowadays electronic government starts dominating in all world countries. Some states are more experienced, while others just started implementing it. Nevertheless, which models the country had reached, all of them should make the progress. It is important to try to overlook and analyse in essence the e-government services maturity and “E-Diamond” models at the public administration level, that are used in various countries. Having studied the peculiarities of stages’ models of electronic government services and having carried out their comparative analysis the work shows the main similarities and differences of the models. Implementation of electronic government services in stage models is grounded on the complexity of service integration – a deeper integration of electronic government services is possible only having stepped through the lower integration stage. Swedish scientists A. Persson and G. Goldkuhl consider this policy of stage integration of services to be a disadvantage and they developed a contrapositional model “E-Diamond” which provides conditions to set free the stages and let them operate individually, not dependent on each other. Stages’ models have different requirements for self-identification in information systems. “ANAO”, “SAFAD”, “Hiller&Belanger” stages’ models require self-identification passing from the second to the third levels, while in stages’ models “Lee&Layne” and “Recreation of Public Sector Processes” requirements for self-identification appear in the second stages of providing electronic government services. Having carried out comparative analysis of all models of electronic government services, there are distinguished six key features of the models, such as possible levels of implementation, attributes of different levels, targeting at the customer, targeting at the inside processes, possibility to evaluate services, technological background. However, out of six features the main ones are considered to be the feature of targeting at the inside organizational processes of self-government and the feature of targeting at the customer. The implementation of the above mentioned features is identified in the models of “Stages” and “E-Diamond”. Both of them are quite equally targeted at restructuring inside processes and meeting the needs of customers. Assessing the models of “Stages” and “E-Diamond” according to this rather neutral targeting, they can be applied in economically developing as well as highly developed countries, thus can be considered to be universal. All in all, despite which model is used, there are lots of areas, where governments should change and improve their implementing models of e-government services. They should look ahead, if they want to do their best at e-government conceptual and strategical policy.